Perception and the Mood of Change - Hollender, Henryk; Kobierska-Maciuszko, Ewa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
It was already four years ago when one of us had a chance to present the design of the new building of the Warsaw University Library on the LIBER seminar in Paris. Nearly four months ago first patrons entered the building. Four years is not much when compared to the 195 years of Warsaw University (and its Library!), but considering us librarians those fours years brought about a real revolution.